(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The study aimed at determining the status of occurrence of the orchid treasure of Bangladesh for providing data for Planning National Conservation Strategy and Development of Conservation Management. 54 orchid species are assessed to be presumably lost from the flora of Bangladesh due to environmental degradation and ecosystem depletion. The assessment of their status of occurrence was made based on long term field investigation, collection and identification of orchid taxa; examination and identification of herbarium specimens preserved at CAL, E, K, DACB, DUSH, BFRIH,BCSIRH, HCU; and survey of relevant upto date floristic literature. These species had been recorded from the present Bangladesh territory for more than 50 to 100 years ago, since then no further report of occurrence or collection from elsewhere in Bangladesh is available and could not be located to their recorded localities through field investigations. Of these, 29 species were epiphytic in nature and 25 terrestrial. More than 41% of these taxa are economically very important for their potential medicinal and ornamental values. Enumeration of these orchid taxa is provided with updated nomenclature, bangla name(s) and short annotation with data on habitats, phenology, potential values, recorded locality, global distribution conservation status and list of specimens available in different herbaria. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 65-84